2013 Humaine Association Conference on Affective Computing and Intelligent Interaction 2013
DOI: 10.1109/acii.2013.160
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition from EEG during Self-Paced Emotional Imagery

Abstract: Here we present an analysis of a 12-subject electroencephalographic (EEG) data set in which participants were asked to engage in prolonged, self-paced episodes of guided emotion imagination with eyes closed. Our goal is to correctly predict, given a short EEG segment, whether the participant was imagining a positive respectively negative-valence emotional scenario during the given segment using a predictive model learned via machine learning. The challenge lies in generalizing to novel (i.e., previously unseen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…[121] It is thus important that aBCI researchers consider improving their de-noising methods, since the mentioned artifacts carry relevant emotional information that can artificially improve the performance of patternrecognition algorithms. This was exemplified by Kothe et al [109], who showed, using dense electrode recordings, that several discriminative EEG sources were originating from muscles. Since the goal is to achieve reliable emotion recognition, those artifacts can be considered as valuable for this task.…”
Section: Brain-computer Interfaces 77mentioning
confidence: 96%
See 1 more Smart Citation
“…[121] It is thus important that aBCI researchers consider improving their de-noising methods, since the mentioned artifacts carry relevant emotional information that can artificially improve the performance of patternrecognition algorithms. This was exemplified by Kothe et al [109], who showed, using dense electrode recordings, that several discriminative EEG sources were originating from muscles. Since the goal is to achieve reliable emotion recognition, those artifacts can be considered as valuable for this task.…”
Section: Brain-computer Interfaces 77mentioning
confidence: 96%
“…We are aware of only two studies which used an interactive situation where the participants were playing games to induce and measure emotions. [27,103] Similarly, two studies [109,110] relied on mental imagery, which is expected to elicit emotional patterns similar to everyday interactions. In all these cases, the experiments were carried out in the lab, and there is thus a strong need to evaluate the performance of aBCI in ecological contexts.…”
Section: Emotion Elicitationmentioning
confidence: 99%
“…In [4] the achieved accuracy of the emotional valence is about 71%. The technique relies on changes in the power spectrum of short-time stationary oscillatory EEG processes within the standard EEG frequency bands.…”
Section: Introductionmentioning
confidence: 89%
“…Average accuracy for arousal and valence, % In [5] 96.2 In [8] 36.5 In [2] 66.5 In [4] 71.3 In this paper 76.4…”
Section: Approachmentioning
confidence: 99%
“…ECOG signals offer excellent temporal resolution and may be able to leverage decoders originally developed for electroencephalography (EEG). Non-invasive EEG has been a very successful approach in affective BCI, with some real-time decoding of emotional information [16,17]. Uncertainty arises because all successful EEG affective decoding has been demonstrated in healthy volunteers.…”
Section: Introduction and Rationalementioning
confidence: 99%